PENERAPAN MODEL PEMBELAJARAN RADEC (READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE) BERBANTUAN MEDIA WORDWALL UNTUK MENINGKATKAN KEAKTIFAN BELAJAR IPAS KELAS IV UPTD SD NEGERI 62 PAREPARE - Eva Aulyah; Natriani Syam; Ila Israwaty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this study is the low level of student activity in the science and natural sciences learning process, which is characterized by a lack of participation in discussions, minimal courage to ask and answer questions, and weak cooperation in groups. This study aims to improve the learning activity of fourth grade students in science and natural sciences subjects through the application of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model assisted by Wordwall media. This study is a Classroom Action Research (CAR) which is carried out in two cycles, each consisting of the planning, implementation, observation, and reflection stages. The subjects of the study were fourth grade students of UPTD SD Negeri 62 Parepare with a total of 26 students. Data were collected through observation, documentation, and reflection, then analyzed qualitatively. The results of the study showed that the application of the RADEC model supported by Wordwall media was able to significantly increase student learning activity. Students became more active in paying attention to teacher explanations, participating in group discussions, asking questions, answering questions, and being able to present the results of group work. Thus, the application of the RADEC model assisted by Wordwall media has proven effective in increasing student learning activity in science and natural sciences learning.